Systematic scoping review of patients’ perceived needs of health services for osteoporosis - Chou, L.; Shamdasani, P.; Briggs, Andrew; Cicuttini, F.; Sullivan, K.; Seneviwickrama, K.; Wluka, A. (Springer, 2017)
Health service planners, administrators and providers need to understand the patients’ perspective of health services related to osteoporosis to optimise health outcomes. The aims of this study were to systematically identify and review the literature regarding patients’ perceived health service needs relating to osteoporosis and osteopenia. A systematic scoping review was performed of publications in MEDLINE, EMBASE, CINAHL and PsycINFO (1990–2016). Descriptive data regarding study design and methodology were extracted and risk of bias assessed. Aggregates of patients’ perceived needs of osteoporosis health services were categorised. Thirty-three studies (19 quantitative and 14 qualitative) from 1027 were relevant. The following areas of perceived need emerged: (1) patients sought healthcare from doctors to obtain information and initiate management. They were dissatisfied with poor communication, lack of time and poor continuity of care. (2) Patients perceived a role for osteoporosis pharmacotherapy but were concerned about medication administration and adverse effects. (3) Patients believed that exercise and vitamin supplementation were important, but there is a lack of data examining the needs for other non-pharmacological measures such as smoking cessation and alcohol. (4) Patients wanted diagnostic evaluation and ongoing surveillance of their bone health. This review identified patients’ needs for better communication with their healthcare providers. It also showed that a number of important cornerstones of therapy for osteoporosis, such as pharmacotherapy and exercise, are identified as important by patients, as well as ongoing surveillance of bone health. Understanding patients’ perceived needs and aligning them with responsive and evidence-informed service models are likely to optimise patient outcomes. © 2017 International Osteoporosis Foundation and National Osteoporosis Foundation.